Cystic Lymphangioma of the Greater Omentum: A Case of Partial Spontaneous Regression and Review of the Literature - Haraesh Maranna; Lovenish Bains; Pawan Lal; Rahul Bhatia; Mohd Yasir Beg; Pritesh Kumar; Varuna Mallya (Case Reports in Surgery)
Introduction. Omental cysts are a part of cystic lymphangiomas and are benign proliferations of ectopic lymphatics without a communication with the normal lymphatic system. They commonly involve the neck in the pediatric population and are uncommon at other sites and occur rarely in adults. Case Presentation. A 42-year-old female with complaints of vague lower abdominal pain for 8 months presented with a soft, nontender swelling of size 22×18 cm in the hypogastrium and umbilical region. Computerized tomography (CT) of the abdomen showed a peripherally enhancing hypodense cystic lesion of size 19×14×12 cm perhaps arising from the mesentery. The cyst had spontaneously reduced in size by about 70% over the next 4 months. During surgery, the cyst of size 10×9×8 cm was present in the greater omentum. Excision was done, and histopathology was suggestive of cystic lymphangioma. Discussion. Cystic lymphangiomas have an incidence of 1/20000 at infancy and 1/100000 to 1/250000 of hospital admissions in adults, and the female-to-male ratio is 2 : 1. In adults, they are found in the age group between 40 and 70 years. Spontaneous regression of omental cysts is very rare and presumably from increased pressure in cysts overcoming incomplete obstructions or by establishment of alternative routes of drainage. Conclusion. As the disease is essentially benign and if there are no significant pressure symptoms, the cysts of short duration can be watched further for regression. Long-standing, symptomatic cysts, nonregression, and diagnostic uncertainty will warrant surgery to confirm the diagnosis and relieve the symptoms.